IMPLANTATION OF ACTIONS FOR CONFRONTING DRUG CONSUMPTION IN PRIMARY HEALTH CARE - Jessica Adrielle Teixeira Santos; Magda Lúcia Félix de Oliveira (Universidade Federal do Paraná, 2013)
The study assessed the implantation of directives for integral care of users of alcohol and other drugs in Primary Health Care, through evaluative research case studies, using the Ministry of Health directives for this public policy. City managers and health professionals from a Primary Care center participated, the majority of whom were women aged between 30 and 49 years, who had spent less than five years in their current positions/ roles. As a parameter, it was recommended that the proportion of answers consistent with the directive would correspond to the extent of implantation: implanted (>80%), dissatisfactory (40% to 79.9%) and critical (< 39.9%). The global extent of implantation of the directives was dissatisfactory (66.9%), however, for the managers (91.6%) and some health professionals (80.5%) this was considered acceptable. The results indicate the need to analyze the role of different equipment which are part of the integral care network.